Ineffective esophageal motility and bolus clearance. A study with combined high‐resolution manometry and impedance in asymptomatic controls and patients. Issue 9 (12th May 2020) - Zerbib, Frank; Marin, Ingrid; Cisternas, Daniel; Abrahao, Luiz; Hani, Albis; Leguizamo, Ana M.; Remes‐Troche, José M.; Perez de la Serna, Julio; Ruiz de Leon, Antonio; Serra, Jordi
Abstract: Background: The definition and relevance of ineffective esophageal motility (IEM) remains debated. Our aim was to determine motility patterns and symptoms associated with IEM defined as impaired bolus clearance. Methods: To define altered bolus clearance, normal range of swallows with complete bolus transit (CBT) on high‐resolution impedance manometry (HRIM) was determined in 44 asymptomatic controls. The results were then applied to a cohort of 81 patients with esophageal symptoms to determine the motility patterns which best predicted altered bolus clearance. Subsequently, in a cohort of 281 consecutive patients the identified motility patterns were compared with patients' customary symptoms. Key Results: In asymptomatic controls, the normal range of swallows with CBT was 50%‐100%. In patients, altered bolus transit (<50% CBT) was only associated with 30% or more failed contractions ( P  < .001). Neither weak peristalsis nor absence of contraction reserve (CR) was associated with altered bolus clearance. The patterns which best predicted altered bolus clearance were failed contractions ≥30% (specificity 88.2% and sensitivity of 84.6%), and ≥70% ineffective (failed + weak) contractions (sensitivity 84.6% and specificity 80.9%). No motility pattern was correlated to symptom scores. Conclusions and Inferences: Based on bolus clearance assessed by HRIM, ≥30% failed contractions and ≥70% ineffective contractions have the best sensitivity and specificity to predict altered bolus clearance. Weak contractions and absence of CR are not relevant with respect to bolus clearance. Abstract : The definition of ineffective esophageal motility is debated. Based on bolus clearance assessed by combined high resolution manometry and impedance, we observed that ≥30% failed contractions and ≥70% ineffective contractions have the best sensitivity and specificity to predict altered bolus clearance.